An expanding role of biomarkers in pulmonary arterial hypertension - Yildiz, Mustafa; Behnes, Michael; Akın, Ibrahim (Current pharmaceutical biotechnology, 2017)
Background: Pulmonary Arterial Hypertension (PAH) is a chronic disease which may cause or result from multiple cardiopulmonary disorders. The disease has complex pathophysiological mechanisms and involves many systematic, cellular and molecular changes. Therefore, it is crucial to find out underlying mechanisms and detect biomarkers to achieve early and proper diagnosis, evaluating disease severity, for follow-up and monitor response to treatment. Many biomarkers for PAH have been investigated but yet no such biomarker has been found specific and easily accessible to use for the patients. This review aims to identify an expanding role of biomarkers in PAH. Method: We searched an expanding role of biomarkers such as asymmetric dimethylarginine (ADMA), von Willebrand factor (vWF) and endothelin for PAH in the literature. Results: Thirty-four actual papers were included in this review for searching an expanding role of biomarkers in the PAH. Conclusion: The search for a proper biomarker for PAH patients is an ongoing process. Currently we do not have a PAH-specific, easily accesible, low-priced biomarker for PAH patients. One of the reasons of that is that PAH has a complex etiology and the diesase eventually alters multiple systems. So far, only BNP/NT-proBNP has been mainly approved and widely used for risk assesment in patients with PAH. Ongoing studies, development in the technology and understanding the underlying mechanisms in the pathophysiology of PAH, will eventually lead us to find proper biomarker(s), for PAH, which will also improve patient outcomes and decrease treatment costs in PAH.